Late-Season Nitrogen Applications Increase Soybean Yield and Seed Protein Concentration - Chiluwal, Anuj; Haramoto, Erin R.; Hildebrand, David; Naeve, Seth; Poffenbarger, Hanna; Purcell, Larry C.; Salmeron, Montserrat (Frontiers in Plant Science, 2021)
Low seed and meal protein concentration in modern high yielding soybean [Glycine max L. (Merr.)] cultivars is a major concern but there is limited information on effective cultural practices to address this issue. Field experiments in 2019 and 2020 evaluated the response of seed and meal protein concentrations to the interactive effects of late-season inputs (control, a liquid B. japonicum inoculation at R3, and 202 kg ha-1 N fertilizer applied after R5), previous cover crop (fallow or cereal cover crop with residue removed), and short- and full-season maturity group cultivars at three US locations (Fayetteville, AR; Lexington, KY; and St. Paul, MN). Inoculant applications at R3 had no effect on seed protein concentration or yield. The N applications increased seed protein concentration by 6 to 15 mg g-1 relative to the control, and maintained meal protein concentrations above the minimum threshold required by the industry. We also observed an unexpected yield increase due to late N fertilization in Arkansas (13%) and Minnesota (11%) relative to the unfertilized control. Cover crops increased, decreased, or had no effect on the yield response to late-season N applications depending on the location and year. This study is the first to demonstrate that low soybean seed and meal protein concentration can be consistently improved with late-season N applications. Further research is necessary to investigate sustainable management practices that increase N availability to soybeans late in the season.